O desejo homoerótico e o seu algoz: as configurações da dor e do gozo no romance En finir avec Eddy Bellegueule, de Édouard Louis - Pereira, Anderson Gustavo Silva Macedo (2022)
The human sexuality was subordinated, until the end of the 18th century, to three spheres of control: medical, religious and moral discourses (FOUCAULT, 2015). Understanding that homosexuality is within this nucleus of submission, even before having a word to identify it, we can say that it was seen as a disease, sin and crime, respectively. The individual who did not obey this system would have to deal with some type of discrimination or even the most severe punishments. Despite numerous advances, today, homosexuals are faced with a cruel duality and each one seeks to fit their own homosexuality within this antagonism: (1) the disobedience to the culture, rebelling against it to live its homosexuality in fullness and, thus, take risks of the most diverse or the opposite; (2) the refusal of its own sexual orientation, denying it even to itself, in order to avoid suffer retaliation and humiliation; there are other possibilities between these two poles, always putting the individual in a place of struggle (against itself, a priori, against the others, a posteriori). Within this context of choices, inconsistencies and conflicts as painful as they are pleasurable, we insert our object of study: the novel En finir avec Eddy Bellegueule (2014), by French writer Édouard Louis, in which these pains and pleasures are (re)produced in childhood and in the adolescence of Eddy, narrator-character. His inaugural sexual experiences, at the age of 10, were lived in a marginalized way in a woodshed in the community of Hallencourt (northern France). At the same time, homophobia victimized him: he suffered psychological and physical violence from his family, colleagues at his school and the residents of the village where he lived. The choice of this corpus is justified by the fact that we have a low number of French works translated in Brazil (TORRES, 2007) compared to the voluminous literary production in French. Studying a French-speaking author in such a context is an attempt to keep the Brazilian public’s interest in French literature and language alive, understanding that access to foreign cultures enriches the national culture. In addition, the study of this work seeks to favor discussions on contemporary French narratives with homoerotic themes in Brazil. Therefore, we proceed to a genealogy of homosexualities. Rescuing the past is necessary to understand the epistemologies of the present, so we walk through time with texts of various scholars on the subject like Dover (1994), Naphy (2006), Mott (2001, 2003), Ceccarelli (2008), Quinet (2013) and Trevisan (2018). In addition, we find in psychoanalysis the appropriate tools to analyze Eddy’s early homoerotic experiences, for that, we turn to selected Sigmund Freud’s works (1905, 1912, 1919, 1930). In opposition to the pleasures of homosexuality, we seek to understand the mechanisms of homophobia (BORRILLO, 2010). Thus, the objective of this study is to identify the configurations of pain and enjoyment of understanding and living homosexuality in a context of social degradation from Eddy’s discourse(s), in order to elucidate how he subjectively conceives his sexual orientation and the consequences of that in this context. The signs of homoeroticism and homophobia are (re)interpreted as traces of a poetics of desire and violence, respectively. We conclude that the pain of belonging to a sexual orientation that differs from what most of the society expects leaves in Eddy Bellegueule irreversible sequels that even lead him to change his name in order to try to leave the past behind.